Sustainable production and distribution practices in Atlantic Canadian short food supply chains: Explorative study - Balcom, Rebecca; Abebe, Gumataw Kifle; Yiridoe, Emmanuel K.; Hartt, Christopher M. (Frontiers in Sustainable Food Systems, 2023)
Introduction How food is produced, processed, distributed, and consumed significantly impacts the sustainability of food supply chains. Short food supply chains (SFSCs) have been promoted as an alternative approach to offer sustainable solutions. However, empirical studies provide mixed evidence, and the findings greatly vary based on context. This study explores the social, economic, and environmental sustainability practices in Atlantic Canada's SFSCs from the perspective of farm businesses (producers). Methods A semi-structured survey was conducted among 64 farmers/producers who participated in Atlantic Canadian SFSCs. Participants were asked what channel they used to sell their products and how far this location is in comparison to the production location if sold to an intermediary, how they believe they could better to improve the sustainability of their production methods, what barriers stood in their way of implementation, and how supply chain supporters could help achieve their sustainability goals. Results The findings show that most farm businesses linked to SFCSs have applied ecologically sound production methods such as organic farming, IPM, or other sustainable practices, including regenerative agriculture and no-till farming. Over two-thirds of farm businesses applied sustainable practices such as pasture rotations, green fertilizers, low-carbon couriers, locally sourced inputs, and compostable or recyclable packaging materials. Farm businesses in the Atlantic Provinces highly value the social sustainability of SFSCs, followed by economic and environmental sustainability. Most farm businesses linked to SFSCs were robust to supply- and demand-side shocks, registered a low number of layoffs and fast recovery of operations, and increased their profits during COVID-19 compared to pre-COVID-19 levels. Yet, several barriers remain, the most important ones being high capital costs and longer payback periods. Other barriers include inconsistent inter-provincial trading restrictions, lack of qualified workers and shrinking agricultural land base. Discussion SFSCs in Atlantic Canadian SFSCs have implemented several sustainable practices in their production and distribution systems. Most of the farm businesses linked to SFSCs are small, are focused on specific product groups, target small towns or rural areas, and rely on direct-on farm sales to individual customers, and thus can play a crucial role by complementing longer food supply chains. By taking SFSCs in Atlantic Provinces as a case, this study expands our understanding of recent efforts and challenges local producers face to adopt sustainable practices in their production and distribution systems.